Effect of Health Education in Performing Detection and First Aid in Puerperal Emergency Toward Knowldge and Skill Among Cadre - Ita Herawati; Martina Kusumah Dewi (STIKep PPNI Jawa Barat, 2023)
Aims: Increasing the utilization of The Maternal and Child Handbook can be done in various ways, including by increasing the participation of cadres, because cadres can become facilitators for mothers and families in obtaining The Maternal and Child Handbook. However, what happens in the field is the low knowledge and skills of posyandu cadres in carrying out detection and first aid during postpartum emergencies. Objectives: To determine the effect of health education about the kia book on the knowledge and skills of posyandu cadres in carrying out detection and first aid for Methods: The study was quasi-experimental in nature, using a single group design. The Nagasari Health Center area provided 30 cadres for this study. This study's sample included 30 cadres from the Nagasari Health Center area. The Wilcoxon test is used in bivariate analysis. Results: The knowledge of posyandu cadres in detecting and providing first aid in postpartum emergencies prior to receiving health education is 1.77 (Insufficient) and the SD value is 0.430, whereas their skills in detecting and providing first aid in postpartum emergencies prior to receiving health education are 1.73 (unskilled) and the SD value is 0.450. The knowledge of posyandu cadres in performing detection and first aid in postpartum emergencies after receiving health education is 1.30 (Good) and the standard deviation is 0.466, while their skills are 1.23 (skilled) and the standard deviation is 0.430. Conclusion: health education regarding the kia book has an influence on the knowledge and skills of posyandu cadres regarding emergency detection and first aid during the postpartum period.